NIKAH SUBARANG AYIE VERSUS NIKAH SYARIAH KONTESTASI SIMBOLIK BERAGAMA YANG TERKALAHKAN DI LIMA PULUH KOTA SUMATERA BARAT - Aidil Alfin; Ali Rahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Pernikahan Subarang Ayie is a marriage that is held across the river in Lareh Sago Halaban District in which the marriage is doing illegally or siri, without any binding administration. The marriage is not carried out in accordance with applicable legal and statutory procedures. The practice of this marriage has been going on for a very long time and has been assisted by the prelude actor who carries out his position as a prince in marriage but did his practice in silence. There are several negative impacts as a result of this marriage, including the loss of children's rights, lose the acknowledgment of man’s responsibilities, the susceptive of underage marriages, the susceptible to divorce, the occurrence of marital sanctification and so on. These conditions give bad impacts on society. This kind of marriage across the river should get attention and removal in the order it is no longer happen.